2013
DOI: 10.14710/ijred.2.3.165-168
|View full text |Cite
|
Sign up to set email alerts
|

Application of Hydrothermal Treatment to High Concentrated Sewage Sludge for Anaerobic Digestion Process

Abstract: ABSTRACT:Tomato and seaweed were produced by utilizing CO2 and heat discharged from power generation using biogas in Toyogawa biomass park, Japan. The biogas was obtained by anaerobic digestion with hydrothermal treatment. The hydrothermal treatment was applied to the high concentrated sewage sludge (22 % total solids (TS) dewatered sludge). The purpose of this study is to clarify the effect of hydrothermal treatment on the qualities of high concentrated sewage sludge, by analyzing particulate organic carbon (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Some authors have verified that the HT treatment could decrease sludge viscosity. 29,30 Park et al 31 investigated the effects of hydrothermally pretreated sewage sludge on the stability and dispersibilty of slurry fuel and reported that the HT treatment improved sludge particle size distribution and stability, affecting the sludge atomization, transportation, and viscosity. The hydrophobicity of sludge could be improved because sludge particles would be carbonized during HT processing.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have verified that the HT treatment could decrease sludge viscosity. 29,30 Park et al 31 investigated the effects of hydrothermally pretreated sewage sludge on the stability and dispersibilty of slurry fuel and reported that the HT treatment improved sludge particle size distribution and stability, affecting the sludge atomization, transportation, and viscosity. The hydrophobicity of sludge could be improved because sludge particles would be carbonized during HT processing.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…That was the reason that the HT sludge has a higher water evaporation rate and negligible shrinkage compared with those of raw sludge. Some authors have verified that the HT treatment could decrease sludge viscosity. , Park et al investigated the effects of hydrothermally pretreated sewage sludge on the stability and dispersibilty of slurry fuel and reported that the HT treatment improved sludge particle size distribution and stability, affecting the sludge atomization, transportation, and viscosity. The hydrophobicity of sludge could be improved because sludge particles would be carbonized during HT processing. , This would also result in the improvement of water diffusion properties inside the HT samples.…”
Section: Resultsmentioning
confidence: 99%